NUTRITIVNI STATUS MAKEDONSKIH ADOLESCENATA I ODNOS PREMA NIVOU OBRAZOVANJA I ZAPOSLENI STATUS NJIHOVIH RODITELJA - Bojadzieva Stojanoska, Biljana; Zhivadinovikj Bogdanovska, Julija; Matveeva, Niki; Zafirova, Biljana; Chadikovska, Elizabeta; Trpkovska, Biljana; Dodevski, Ace; Paunkovska, Anamarija (ANTROPOLOŠKO DRUŠTVO SRBIJE, Niš / ANTHROPOLOGICAL SOCIETY OF SERBIA, Niš, 2023)
The aim of this study was to evaluate the nutritional status in Macedonian adolescents and relation with the level of education and employments status of their parents. In this study 1207 adolescent students (616 males and 591 females) at age of 11 to 14 years were included. We measured weight and height using standard procedures while body mass index was calculated and these values were used to assess nutritional status. The examinees fill the questionnaire with the data for parent’s education and employment. We found significant difference between male students who were with risk of obesity and overweight, with high persentage of students with employed mother, contrary to those students with unemployed mother. According to the level of education in father, there was significant difference in the group of underweight females with the higher percentage being underweight with father with lower education, primary school, and only 1,4% were underweight with father with university education. Our data suggest that parental level of education and employment status are in relation with the nutritional status of Macedonian adolescents.
NUTRITIONAL STATUS OF MACEDONIAN ADOLESCENTS AND RELATION TO LEVEL OF EDUCATION AND EMPLOYMENTS STATUS OF THEIR PARENTS
Kopaonik (Brzeće), September 27rd-30th 2023
Keywords: adolescent; underweight; nutritional anthropometry; obesity